2012
DOI: 10.1080/01635581.2012.711418
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Intake Is Negatively Associated with Promoter Methylation of the Wnt Antagonist GeneDKK1in a Large Group of Colorectal Cancer Patients

Abstract: Diet and lifestyle help mediate colorectal cancer (CRC) risk but the molecular events that mediate these effects are poorly characterized. Several dietary and lifestyle factors can modulate DNA methylation suggesting that they may influence CRC risk through epigenetic regulation of cancer-related genes. The Wnt regulatory genes DKK1 and Wnt5a are important contributors to colonic carcinogenesis and are often silenced by promoter hypermethylation in CRC; however, the dietary contributions to these events have n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
36
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 32 publications
2
36
0
Order By: Relevance
“…The silencing of DKK-1 expression has been related to histone deacetylation and DNA hypermethylation (45,46). Recent studies also indicated the possible association of histone methylation with DKK-1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…The silencing of DKK-1 expression has been related to histone deacetylation and DNA hypermethylation (45,46). Recent studies also indicated the possible association of histone methylation with DKK-1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, DKK1 methylation was found to be a robust marker for the prediction of recurrence in stage II colon cancer patients [36]. It is reported that dietary vitamin D intake was strongly negatively associated with DKK1 methylation and may alter colon cancer risks [11]. These modulations by T3E might be a valuable strategy to overcome the therapeutic resistance of MM [37, 38].…”
Section: Discussionmentioning
confidence: 99%
“…In a large cohort study of colorectal cancer patients, vitamin D intake was negatively associated with DKK1 promoter methylation [11]. It is thought that vitamin E, which possesses anti-cancer properties, also affects epigenetic factors [12].…”
Section: Introductionmentioning
confidence: 99%
“…Histone modification and promoter CpG methylation alter cancer-related gene expression and are frequently involved in carcinogenesis [58] . So far, downregulation of Wnt antagonist genes associated to promoter hypermethylation have been identified in a variety of malignancies, such as renal, bladder, lung, breast, colorectal, gastric and neuroblastoma [59][60][61][62][63][64][65] . Furthermore, the Wnt/b-catenin pathway genes are found among those affected by dysregulation of microRNAs (miRNAs) in many kinds of cancers, and particularly, expression profiling has shown that certain miRNAs are associated with gastric cancer development, progression and response to therapy [66][67][68] .…”
mentioning
confidence: 99%